20 years on São Tomé and Príncipe has voted again for “change” - Seibert, Gerhard (2010)
In December 1989, São Tomé and Príncipe was the first African one-party state to hold a National Conference and decide on a transition to multiparty democracy. On January 20th 1991, the archipelago was the second African country – after Cape Verde a week prior – to hold democratic elections. Since then, both legislative and presidential elections have been organized regularly and peacefully. All these elections – financed by foreign donors – have been considered by international observers as free, fair and transparent.